Partial replacement effect of dietary fish meal with blood meal on growth performance, body composition, and haematology of butter catfish Ompok bimaculatus - Hossain, Md. Mubarak; Udoy, Fazla Rabby; Islam, Md. Rabiul; Akter, Taslima; Alam, Md. Shafiqul; Alam, Md. Shahanoor; Sarker, Md. Shah Alam; Hossain, Md. Amzad (Journal of Fisheries, 2025)
Escalating costs and the constrained supply of fish meal have underscored the imperative to identify alternative, economically viable protein sources for aquafeeds. This study evaluates the feasibility of incorporating blood meal as a partial replacement for fish meal in the diet of butter catfish (Ompok bimaculatus). Five iso-nitrogenous (35.0%) and iso-lipidic (7.0%) diets, designated T0 (control), T5, T10, T15, and T20, were prepared by substituting fish meal protein at 0, 5, 10, 15, and 20% levels with blood meal protein, respectively. Fish groups were assigned to each of the formulated diets in triplicate. Each of the 15 glass aquariums (180 L) was stocked with 50 fish (mean±SD 1.5±0.03 g) and fed with experimental diets for eight weeks. The fish fed the T15 diet achieved the highest weight gain (4.61±0.22 g), percent weight gain (305.30±1.20%), and specific growth rate (1.42±0.21% day–1) compared to fish fed all other diets. The lowest feed conversion ratio (1.85±0.08) was observed in fish fed T10 diet. The highest protein efficiency ratio (1.88±0.02) was also observed in fish fed T15 diet. Replacing fish meal with blood meal positively impacted the haematological profile and whole-body proximate composition. Additionally, the cost of the experimental diets was reduced compared to the control diet. Regression analysis indicated that the optimal replacement level of fish meal protein with blood meal protein ranged from 10.8% to 12.6%. We suggest that blood meal can be effectively used as a partial fish meal substitute in the aquafeed, offering a cost-effective and sustainable alternative.